The Adams Federalists - Dauer, Manning J. (Johns Hopkins University Press, 2019)
Originally published in 1953. Between 1789 and 1803, the United States existed as a developing national state, sparsely settled. The de facto precedents of America's nascent political system had not yet been fleshed out by the generation of statesmen who paved its political way. Historians have examined the rise of the party system in US politics by emphasizing the Jeffersonians, who-led by Thomas Jefferson-helped to develop an agrarian voting bloc. In The Adams Federalists, Manning J. Dauer attends to Adams's struggles with the Federalist Party, arguing that his term is the key to understanding the success of the Jeffersonians in promoting their own democratic ideals. Dauer attributes the fall of Federalism to Adams's failure to maintain a moderate cohort in the White House. The Federalist Party's leadership increasingly adopted policies that isolated the Federalists' agrarian supporters, who in turn found support in the Jeffersonians' archaic politics. Professor Dauer provides an alternative explanation for the popularity of Jefferson's political faction and argues that economic factors undergirded the political organization of early America's voting base. Since its publication, scholars have recognized The Adams Federalists as a definitive study of the Federalist Party during the Adams administration.